Body weight dynamics of Zebu and crossbred cows in relation to postpartum reproduction under sub humid climate of Bako - Gebreyohannes, G.; Tegegne, Azage; Diedhiou, M.L.; Hegde, B.P. (Ethiopian Society of Animal Production, 2003)
Postpartum body weight dynamics of zebu and crossbred cows in relation to postpartum reproduction was studied using data from the Bako Agricultural Research Centre. Body weight at calving, first postpartum oestrus, first service and conception were analysed using the General Linear Model which included cow breed, parity, and calving season and year as a fixed effects and calving weight and body weight gain from calving to three months as a covariate. Accordingly, the result indicated that the overall mean body weights at calving, estrus, service and conception were 299.7 t 1.35, 304.6 ± 0.61, 309.5 ± 0.79 and 313.3 ± 0.90 kg, respectively. Boran Simmental cows had significantly (p < 0.001) the heaviest weight at calving (381.3 t 5.95 kg), estrus (322.3 ± 3.07 kg), service (330.6 t 4.00 kg) and conception (344.2 t 4.56 kg), while Horro cows had the lightest weight. Significantly (at least p < 0.05) higher calving weight was recorded for cows that calved during June to August while the highest service and conception weights were recorded for cows that calved during December to February. Cows in the first parity had significantly (p < 0.05) lighter weight at calving, estrus, service and conception compared to cows in the other parities. Body weight at estrus, service and conception were linearly and significantly (p < 0.001) related to body weight at calving and body weight gain from calving to three months. All breeds except Horro and Horro Jersey cows lost a portion of their calving weight at estrus (0.3 to 16.3 %), service (3.7 to 13.3 %) and conception (0.9 to 11.5 %). The Jersey lost 0.3% of its calving weight at estrus but gained 1.5 and 2% of their calving weight at first service and conception. From this study it can be concluded that cows had to attain the critical postpartum body weight to resume reproduction and conceive. Besides, the critical weight at conception is higher than at first postpartum estrus and service. Cows had to gain a portion of their calving weight lost to resume reproduction.